COMPARISON BETWEEN BIOLOGICAL AND CHEMICAL SYNTHESIS OF ZINC OXIDE NANOPARTICLES AND ITS INFLUENCE OVER SOME ANTIBIOTICS - A.B. ABEER MOHAMMED (International Journal of Pharma and Bio Sciences, 2015)
This study reports comparison between bio and wet chemical synthesis of Zinc Oxide nanoparticles (ZnO NPS) biological synthesis by using cell free supernatant some isolate of bacillus cereus that have ability to convert zinc acetate to ZnO (NPS). On the other hand, wet chemical synthesis using zinc nitrate and sodium hydroxide as a surrogate. In this report we used two methods for improve antibiotics that effect against pathogenic bacteria. The present investigation describes the maximum zone of inhibition was observed in the bio ZnO NPs (5 µL) with antibiotics kanamycin (K).The effects of some antibiotics have more affected with ZnO nanoparticles about without and bacteria become more sensitive to some antibiotics in the same concentration.